Particular Approaches to the System of International Humanitarian Law Special Principles: Substance and Evolution - A. Yu. Yastrebova (Московский журнал международного права, 2022)
INTRODUCTION. The list and the contents of branch (special) principles of IHL are considered to be a current subject of study. Along with the traditional legal approaches, the study forward additional theoretical arguments to include the environmental protection and the responsibility of officials and militaries for war crimes in the system of IHL principles. Besidesthat, it is obvious that the record of IHL prohibitions to belligerents as general international legal rules to conduct hostilities, is refined.   MATERIALS AND METHODS. The above study is based both on scientific researches of Russian and foreign authors in the field of IHL and analysis of international legal acts on universal level. Methodological basis of research includes general scientific methods (analysis and synthesis, induction and deduction, modeling and systematization) and special legal methods (legal comparativistics, formal legal).   RESEARCH RESULTS. Completed systematization of IHL principles shows combination of different legal concepts, either of which has a certain scientific value. It looks important to summarize the international legal sources and trends taking place in UN system in order to expand the list of the mentioned principles.   DISCUSSION AND CONCLUSIONS. In frames of this study the author is proposing the impartial assessments of established scientific approaches to definition and contents of IHL branch (special) principles. Both the forms of international legal cooperation of states to create an institution of responsibility for war crimes and the results of Nuremberg military tribunal regarding prevention of IHL violations are examined separately. The complimentary legal grounds of modern international courts functioning are determined by combination of national and interstate jurisdiction in the above field.